Methods for secure cloud processing of big data - Yerzhan N. Seitkulov; Seilkhan N. Boranbayev; Gulden B. Ulyukova; Banu B. Yergaliyeva; Dina Satybaldina (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
We study new methods of secure cloud processing of big data when solving applied computationally-complex problems with secret parameters. This is one of the topical issues of secure client-server communication. As part of our research work, we model the client-server interactions: we give specific definitions of such concepts as “solvable by the protocol”, “secure protocol”, “correct protocol”, as well as actualize the well-known concepts-“active attacks” and “passive attacks”. First, we will outline the theory and methods of secure outsourcing for various abstract equations with secret parameters, and then present the results of using these methods in solving applied problems with secret parameters, arising from the modeling of economic processes. Many economic tasks involve processing a large set of economic indicators. Therefore, we are considering a typical economic problem that can only be solved on very powerful computers.